2000
DOI: 10.1097/00043426-200003000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Castleman Disease and Systemic Lupus Erythematosus Phenotype in a Boy With Klinefelter Syndrome: Long-term Disease Stabilization With Interferon Therapy

Abstract: An 11-year-old boy with Klinefelter syndrome had Castleman disease (CD) of plasma cell type develop. Nonregulated antibody production mimicked systemic lupus erythematosus (SLE). Hepatitis C virus (HCV) infection caused significant disease worsening. The patient was treated with a daily dosage of 2 million units/m2 of IFN-alpha. Dramatic clinical improvement and decreasing autoimmune phenomenon were observed. HCV RNA were cleared. Hypergammaglobulinemia did not change. The boy has been living for 8 years with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…5 Treatment with interferon-␣ or with the anti-CD20 monoclonal antibody rituximab (Rituxan; Hoffman-La Roche, Basel, Switzerland) has resulted in durable clinical remission of the disease; however, these findings are based on a small number of patients. 11,12 Interleukin-6 (IL-6) is a pleiotropic cytokine with a wide range of biologic activities, including support of hematopoiesis and regulation of immune responses. 13 Dysregulated overproduction of IL-6 from germinal center B cells is implicated in the pathogenesis of plasma-cell-type Castleman disease.…”
Section: Introductionmentioning
confidence: 99%
“…5 Treatment with interferon-␣ or with the anti-CD20 monoclonal antibody rituximab (Rituxan; Hoffman-La Roche, Basel, Switzerland) has resulted in durable clinical remission of the disease; however, these findings are based on a small number of patients. 11,12 Interleukin-6 (IL-6) is a pleiotropic cytokine with a wide range of biologic activities, including support of hematopoiesis and regulation of immune responses. 13 Dysregulated overproduction of IL-6 from germinal center B cells is implicated in the pathogenesis of plasma-cell-type Castleman disease.…”
Section: Introductionmentioning
confidence: 99%
“…CD, which also refers to giant lymph node hyperplasia, is described as an atypical lymphoproliferation disorder that may present with or without systemic symptoms. Some reports have showed that multicentric CD has a close association with several autoimmune conditions such as thrombocytic thrombocytopenic purpura, rheumatoid arthritis, pemphigus vulgaris and membranous nephropathy [2,3]. In this report, we present a patient with SLE combined with CD morphology.…”
Section: Introductionmentioning
confidence: 81%
“…In the 1990s, systemic treatment for MCD included chemotherapy based on regimens for lymphoma such as cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) (1)(2)(3)(4). Treatment with a monoclonal antibody diNephrology Center, Toranomon Hospital Kajigaya, Japan and Okinaka Memorial Institute for Medical Research, Toranomon Hospital Kajigaya, Japan (12).…”
Section: Introductionmentioning
confidence: 99%